Analysis of the Influence of Key Audit Matters on Audit Report Lag with Audit Committee Characteristics as a Moderating Variable - Kamila Safitri Dewi; Helianti Utami (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to show the effect of disclosing Key Audit Matters on Audit Report Lag and the moderating role of audit committee characteristics in 651 non-financial companies on the IDX (2022-2023) using Moderated Regression Analysis. The results show that KAM has a significant negative effect on ARL, indicating that KAM disclosure accelerates audit completion. However, the frequency of committee meetings and member busyness do not moderate this relationship. The size of the audit committee actually strengthens the negative effect of KAM-ARL, although contrary to the hypothesis. These findings strengthen the empirical evidence that KAM improves audit efficiency, while the effectiveness of the audit committee is more determined by the number of members than the frequency of meetings or individual workload. The study provides practical implications for the preparation of timely financial reports through optimization of KAM disclosure and audit committee structure.